Analysis of Trends in Pneumonia Cases in Toddlers in Maros Regency, South Sulawesi Province 2018-2021 - Putri Yuliyanti Liambo; Inayah Zahrah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Pneumonia is a lower respiratory tract infection and remains a leading cause of mortality among children under five, particularly in developing countries. Maros Regency is among the regions with a relatively high incidence of pneumonia in this age group. Objective: This study aims to analyze the spatial and temporal distribution of pneumonia cases among children under five in Maros Regency during 2018–2021, and to identify factors contributing to variations in case distribution. Methods: This research employed a quantitative descriptive design using secondary data from the Maros Regency Health Profile for 2018–2021. Data were analyzed descriptively through tables and graphs to illustrate the distribution of pneumonia cases over time. Results: The findings revealed annual fluctuations in pneumonia incidence among children under five, with the highest number of cases recorded in 2021. Several factors were identified as influencing the distribution of cases, including environmental conditions, access to healthcare services, community knowledge levels, and the capacity of health facilities. Conclusion: Efforts to address pneumonia among children under five in Maros Regency should focus on improving access to healthcare services, strengthening the referral system, and enhancing community education on prevention and early detection. Expanding early detection programs and building the capacity of healthcare workers are also essential. Keywords: Pneumonia, children under five, healthcare facilities, accessibility, Maros Regency, Indonesia